What they really teach you at the Harvard Business School - Kelly, Francis J.; Kelly, Heather Mayfield (London : Grafton Books, 1986)
This valuable book offers all business people the opportunity to find out the concepts and methods that make Harvard graduates so well respected-and to apply them to their own business practice.
Includes bibliographical references.
hza 04/09/2018
Loans
Keywords: Management; Business policy; Managerial economics